The Oath [videorecording (DVD)] - Barinholtz, Ike, 1977-; Barinholtz, Ike, 1977-; Haddish, Tiffany, 1979-; Dunn, Nora, 1952-; Ellis, Chris, 1956- (Lions Gate Entertainment, 2019)
When Chris, a high-strung 24-hour progressive news junkie, and his more levelheaded wife Kai learn that citizens are being asked to sign a loyalty oath to the president, their reaction is disbelief, followed by idealistic refusal. But as the Thanksgiving deadline to sign approaches, the combination of sparring relatives, Chris's own agitation, and the unexpected arrival of two government agents sends an already tense holiday dinner gathering completely off the rails.